PARTISIPASI POLITIK MAHASISWA UNIVERSITAS NEGERI PADANG SEBAGAI BAGIAN DARI KEKUATAN POLITIK DALAM MEMPENGARUHI KEBIJAKAN RKUHP - Rima Arfa Solia; Lince Magriasti (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
The RKUHP policy is the result of a regulation made by the DPR in 2019 at the end of its term of office, because the content of this regulation contains a lot of ombiguity and is controversial by students asking the government to re-examine this regulation, participation by students becomes a political force when the president finally takes it. action by resigning the endorsement of this policy to conduct a review, in practice the students of the State University of Padang (UNP) were a part of political power at that time, various ways of participation such as demonstrations, discussions, and the use of social media were carried out by UNP students. The biggest factor that affects the participation of UNP students is experience in organizations and the influence of information on social media. It is recognized that UNP students have high political awareness but it is inversely related to the relatively low trust in the government, thus giving birth to a form of militant-radical political participation